‘Power-sensitive design principles’ for climate change adaptation policy-making in South Asia - Sumit Vij; Robbert Biesbroek; Ryan Stock; Maaz Gardezi; Asif Ishtiaque; Annemarie Groot; Katrien Termeer (Earth System Governance, 2021)
Abstract:: Despite the proliferation of power approaches to study climate change, there is little focus on how to deal with the negative effects of power in climate change adaptation (CCA) policy-making. CCA literature provides little insight into understandings of manifestations of power that can create negative effects, especially in the context of South Asia. This review answers the question: How can CCA policy actors deal with the negative effects of power during the policy-making process? We used a two-layered systematic literature review to identify various manifestations of power that are responsible for negative effects in CCA policy-making in South Asia and to determine power-sensitive design principles (PDPs) to address these manifestations of power. We conclude that although the four PDPs are no panacea for dealing with the negative manifestations of power, they are useful considerations when engaged in long-term CCA policy processes.